Propaganda política y personal en las emisiones monetarias de Trajano y Adriano (Estudios humanísticos. Geografía, historia y arte, 1993)
The second century D.C., has been called with every right "The Golden Age of the Antoninos"; indeed, during this century a unique class emerges in Universal History: That of philosopher - emperors or friends of the philosophers. Their activities during their mandates were always governed by the principie of philosophical humanism. This is what we are trying to demonstrate in this articie.